2020
DOI: 10.1111/mve.12474
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and photoperiod effects on dormancy status and life cycle parameters in Aedes albopictus and Aedes aegypti from subtropical Argentina

Abstract: Aedes albopictus (Diptera: Culicidae) distribution is bounded to a subtropical area in Argentina, while Aedes aegypti (Diptera: Culicidae) covers both temperate and subtropical regions. We assessed thermal and photoperiod conditions on dormancy status, development time and mortality for these species from subtropical Argentina. Short days (8 light : 16 dark) significantly increased larval development time for both species, an effect previously linked to diapause incidence. Aedes albopictus showed higher mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…More specifically, based on the analysis, the studies by Sivan et al ( 63 ), Sivan et al ( 62 ), Phanitchat et al ( 55 ), Yang et al ( 67 ), and De Majo et al ( 38 ) showed no significant higher risk difference between the maximum and minimum. On the other hand, studies by Bagny Beilhe et al ( 31 ), Byttebier et al ( 33 ), Campos et al ( 34 ), De Majo et al ( 37 ), Garzón et al ( 42 ), and Muttis et al ( 53 ) showed that there was no significant lower risk difference between the maximum and minimum temperatures respectively.…”
Section: Resultsmentioning
confidence: 95%
“…More specifically, based on the analysis, the studies by Sivan et al ( 63 ), Sivan et al ( 62 ), Phanitchat et al ( 55 ), Yang et al ( 67 ), and De Majo et al ( 38 ) showed no significant higher risk difference between the maximum and minimum. On the other hand, studies by Bagny Beilhe et al ( 31 ), Byttebier et al ( 33 ), Campos et al ( 34 ), De Majo et al ( 37 ), Garzón et al ( 42 ), and Muttis et al ( 53 ) showed that there was no significant lower risk difference between the maximum and minimum temperatures respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Com o aumento da pluviosidade e a diminuição na temperatura, a proliferação de A. aegypti é favorecida pelo aumento da disponibilidade de criadouros propícios para oviposição da fêmea . Nos períodos de aumento de temperatura e escassez de chuvas, o desenvolvimento dos vetores fica comprometido, é quando os ovos podem entram em diapausa à espera de períodos com ocorrência de chuvas em que as larvas eclodem (Garzón et al, 2021).…”
Section: Discussionunclassified
“…Thus, the cold tolerance and hence the fitness advantage of the high altitude population in Nepal (details on the cold tolerance potential of the Nepalese populations: (42)) may further increase (27), as also indicated by the establishment of a more cold resistant population of Ae. aegypti in a temperate region in Argentina (Buenos Aires; (18,72,73)). Such a phenotype would increase the introduction risk of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…For Ae. aegypti it has already been documented that populations can invade novel habitats by following their climate niches as a consequence of global warming (11, 18), moreover their expansion to new regions in the future is likely (19, 20). Further expansion to cooler ecoregions such as Europe will additionally require the adaptation to cooler temperatures (21, 22).…”
Section: Introductionmentioning
confidence: 99%